Ukuran Perusahaan Pada Kualitas Laporan Keberlanjutan Perusahaan Sektor Energi di Indonesia Dengan Harga Saham Sebagai Moderasi - Jumarsih Jumarsih; Zuhrotun Zuhrotun; Sutoyo Sutoyo (AKUNTANSI 45, 2025)
This study aims to examine the effect of company size on the quality of sustainability reports in energy sector companies listed on the Indonesia Stock Exchange (IDX), and to analyze the role of stock prices as a moderating variable in this relationship. The theory used as the main basis is stakeholder theory, which states that companies have a responsibility to disclose sustainability information in order to meet stakeholder expectations. This study uses a quantitative approach with the Moderated Regression Analysis (MRA) method. The research sample was selected by purposive sampling in energy sector companies that published sustainability reports and financial reports in the period 2021–2023. Company size is measured by the natural logarithm of total assets, sustainability report quality is measured by the disclosure score using the GRI standard, while stock price is measured by the natural logarithm of the year-end closing price. The results show that company size has a positive effect on the quality of sustainability reports, and stock price significantly strengthens the relationship. These findings support stakeholder theory, that larger companies with high market value tend to provide greater transparency to stakeholders through better quality sustainability reporting.